ANALISA TINGKAT PERTUMBUHAN RUMPUT LAUT JENIS GRACILARIA sp DENGAN METODE BUDIDAYA YANG BERBEDA - Dewi Purnama; Zamdial T (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2013)
The objectives of this study was to know the growth rate and production of sea weed of Gracilaria sp species that cultured by Floating and Off Bottom Methods. This research was conducted in Pulau Baai Waters Bengkulu City during 2 (two) month. The data were analyzed statistically by using Completely Randomized Design. Based on the result of variance analysis were obtained that Ftest value = 22.369 that more than Ftable value at 5% level = 4.45 and 1% level = 8.40 for degree of freedom (1.17). So, it’s mean that there are significant and very significant between both treatments, where Floating Method showed production and growth rate are the best than Off Bottom Method.